2013
DOI: 10.1007/s00125-013-2874-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in a Chinese population identifies a susceptibility locus for type 2 diabetes at 7q32 near PAX4

Abstract: Aims/hypothesisMost genetic variants identified for type 2 diabetes have been discovered in European populations. We performed genome-wide association studies (GWAS) in a Chinese population with the aim of identifying novel variants for type 2 diabetes in Asians.MethodsWe performed a meta-analysis of three GWAS comprising 684 patients with type 2 diabetes and 955 controls of Southern Han Chinese descent. We followed up the top signals in two independent Southern Han Chinese cohorts (totalling 10,383 cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…This association was exclusive to East Asians, in whom the 192His allele is, in fact, common (MAF~10%) with a substantial effect size (allelic OR=1.79 [1.47-2.19]); 192His is virtually absent in other ancestries (MAF=0.014%). The rs2233580 association replicated in independent East Asian case-control data (n=3,301; p=5.9×10 −7 : Supplementary 9) and was distinct (r 2 <0.05) from previously-reported GWAS SNVs at the GCC1-PAX4 locus 6,8 . PAX4 encodes a transcription factor involved in islet differentiation and function 17 (Supplementary 10), and PAX4 variants have been implicated in early-onset monogenic diabetes 18 .…”
Section: Analysis Of Coding Variationsupporting
confidence: 55%
See 1 more Smart Citation
“…This association was exclusive to East Asians, in whom the 192His allele is, in fact, common (MAF~10%) with a substantial effect size (allelic OR=1.79 [1.47-2.19]); 192His is virtually absent in other ancestries (MAF=0.014%). The rs2233580 association replicated in independent East Asian case-control data (n=3,301; p=5.9×10 −7 : Supplementary 9) and was distinct (r 2 <0.05) from previously-reported GWAS SNVs at the GCC1-PAX4 locus 6,8 . PAX4 encodes a transcription factor involved in islet differentiation and function 17 (Supplementary 10), and PAX4 variants have been implicated in early-onset monogenic diabetes 18 .…”
Section: Analysis Of Coding Variationsupporting
confidence: 55%
“…Over the past decade, successive waves of T2D GWAS -featuring ever larger samples, progressively denser genotyping arrays supplemented by imputation against more complete reference panels, and richer ethnic diversity -have delivered >80 robust association signals [2][3][4][5][6][7][8] . However, in these studies, the alleles interrogated for association are predominantly common (minor allele frequency [MAF]>5%), and with limited exceptions 7,9 , the variants driving known association signals are also common, with individually-modest impacts on T2D risk [2][3][4][5][6][7][8]10 . Variation at known loci explains only a minority of observed T2D heritability 2,3,11 .…”
mentioning
confidence: 99%
“…Findings from the current study and those reported by the GoT2D and T2D-GENES consortia suggest that PAX4 also harbours common variants that confer susceptibility to type 2 diabetes. Interestingly, in a previous GWAS of East Asians, the risk allele of a common variant, rs10229583, located downstream of PAX4, was reported to be associated with higher risk of type 2 diabetes and a younger age of diagnosis [33]. Among the 3652 cases in the current study, individuals who carried the risk allele (T) of the PAX4 missense variant rs2233580 were also significantly younger at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 42%
“…PAX4 has been shown to repress the transcriptional activity of insulin [19] and glucagon [31] promoters. PAX4 is located at 7q32, a region reported to be associated with type 2 diabetes in previous GWAS of Asians [32,33]. An intergenic variant rs6467136 located near GRIP and GCC1-PAX4 was reported to be associated with type 2 diabetes in a meta-analysis of eight GWAS in East Asians [32], whilst rs10229583, located downstream of PAX4, was identified as a risk variant in a GWAS for type 2 diabetes in a Chinese population [33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation